The Effect of Using Data Journalism on Journalists Working in Jordanian News Websites - Alzubi, Ahmad (Department of Communications, Universitas Islam Indonesia, 2023)
Over the last several years, the concept of data journalism has garnered a significant attention from academics as an innovative journalistic practice. This study investigates the effects of the use of data journalism on journalists working in Jordanian news websites. The study applied quantitative method in collecting data from a sample of one hundred journalists employed by Jordanian news websites. This study finds that the use of data journalism has significant and advantageous effects on the journalists’ performance, especially through the enhancement of the accuracy and dependability of their reporting, the improvement of their narrative aptitude, and the refinement of their skill in providing data analysis. This study also identifies some challenges that journalists should deal while engaging in the practice of data journalism, including the lack of adequate training and competency in data analysis, restricted supply and accessibility of data, and technical infrastructure of news websites.